Microbial Diversity of Bacterial Species (Rhizobium and Azospirillum) under Different Agroforestry Land Use Systems - Priya,; , S.B. Agrawal; , Vishnu Solanki; , Ashish Kumar; , B.S. Dwivedi; , Ajay Kumar Shah; , Kamal Kishor Patel; , Sanjay Singh Jatav (Archives of Current Research International, 2024)
This investigation is associated with the microbial diversity of different agroforestry systems. The study interpreted the changes of bacterial population during the duration of the experiments. This study was analyzed by CRBD (Complete Randomized Block Design) with 5 treatments (i.e. agroforestry systems) and 4 replications. The research was conducted on cropping systems at JNKVV, Jabalpur, and the Forest Research Farm during the Rabi season of 2021-22 and 2022-23. Soil collection was carried out at a depth of Rhizosphere soil (0 to 15 cm) in different agroforestry systems; later on, the soil was tested through the use of serial dilution methods. The bacterial population influence to the decomposition of leaf litter and straw material in the soil.The result revealed that the Rhizobium species population was found in maximum T1-D. sissoo- wheat (66.28 and 66.96 X 107 cfu g-1) in the respective years of 2021-22 and 2022-23, followed by the sequence of population of Rhizobium spp. had T3 (M. pinnata-Wheat) > T2 (G. arborea-Mustard) > T5 (M. indica-linseed) > T4 (A. nilotica-wheat) estimated under agroforestry systems. The Azospirillum species population increases year to year under the agroforestry system. the population sequence under agroforestry system had T1 (D. sissoo-wheat) >T3 (M. pinnata-wheat) > T2 (G. arborea-mustard) > T5 (M. indica-linseed) > T4 (A. nilotica-wheat) obtained under agroforestry systems. The overall conclusion of this investigation is that the bacterial population is obtained under maximum in the D. sissoo with wheat-based agroforestry systems.